2020
DOI: 10.1038/s41597-020-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

An improved high-quality genome assembly and annotation of Tibetan hulless barley

Abstract: Hulless barley (Hordeum vulgare L. var. nudum) is a barley variety that has loose husk cover of the caryopses. Because of the ease in processing and edibility, hulless barley has been locally cultivated and used as human food. For example, in Tibetan Plateau, hulless barley is the staple food for human and essential livestock feed. Although the draft genome of hulless barley has been sequenced, the assembly remains fragmented. Here, we reported an improved high-quality assembly and annotation of the Tibetan hu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Interestingly, the barley nsLTP gene ( blt4 ) was also found in the cold stress response [ 27 , 28 ]. The latest physical, genetic and functional sequence assemblies of the barley and Qingke genomes were completed in 2012 and 2016 [ 29 , 30 ] and 2015, 2018, and 2020 [ 22 , 31 , 32 ], respectively, and they provided an important reference for future crop breeding, improvement, gene function and evolution research.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the barley nsLTP gene ( blt4 ) was also found in the cold stress response [ 27 , 28 ]. The latest physical, genetic and functional sequence assemblies of the barley and Qingke genomes were completed in 2012 and 2016 [ 29 , 30 ] and 2015, 2018, and 2020 [ 22 , 31 , 32 ], respectively, and they provided an important reference for future crop breeding, improvement, gene function and evolution research.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the full length HvWRKY6 gene sequence from CI5791, Morex, and Tifang were identical ( Supplementary Figure 1 ) suggesting that the gene is conserved for its primary aa sequence across both resistant and susceptible barley genotypes. BLAST analysis of the barley pan-genome ( Jayakodi et al, 2020 ) showed 100% sequence identity for the lines Akashinriki, Barke, Golden Promise, Hockett, HOR 3081, HOR 3365, HOR 7552, HOR 8148, HOR 9043, HOR 10350, HOR 13821, HOR 13942, HOR 22559, Igri, OUN333, RGT Planet, ZDM02064 ( Jayakodi et al, 2020 ; Schreiber et al, 2020 ), Bowman ( IBGSC, 2012 ), Haruna Nijo ( Sato et al, 2016 ), and Lasa Goumang ( Zeng et al, 2020 ). Whereas, ZDM01467 ( Jayakodi et al, 2020 ) contained two concatenated hits of highly identical sequences suggesting a mis-assembly of the region.…”
Section: Resultsmentioning
confidence: 99%
“…Each demultiplexed file was further mapped to a published reference of Hordeum vulgare (GenBank assembly accession: GCA_004114815.1 [55]) using BWA v.0.7.12-r1039 [56] with default settings, after first indexing the reference using the option '-a bwtsw' for a long reference genome. The aligned sam files were sorted by reference coordinates, and read groups were added into their headers with Picard tools.…”
Section: Snp Filteringmentioning
confidence: 99%